Elephant-Initiated Interactions with Humans: Individual Differences and Specific Preferences in Captive African Elephants (Loxodonta africana) - Rossman, Zoë T.; Padfield, Clare; Young, Debbie; Hart, Lynette A. (Frontiers in Veterinary Science, 2017)
South Africa has seen a recent increase in the number of African elephants (Loxodonta africana) maintained in reserves and parks and managed in free contact, where they may spend a significant amount of time in close proximity to humans. This study investigates how individual elephants choose to initiate interactions with humans by examining whether interaction types and frequencies vary both between elephants and with regards to the category of human involved in the interaction. Observations were made on a herd of seven captive African elephants frequently exposed to elephant handlers (guides), volunteers (who carry out general observations for the park’s research unit), and tourists. The elephants differed in the frequencies with which they initiated interactions with each category of human and in the types of behaviors they used to initiate interactions. However, all of the elephants interacted most frequently with guides. Certain individual elephants showed preferences in interacting with specific guides, indicating particular elephant-guide bonds. This study provides evidence for elephant-handler bonds as well as information on the extent of interactions between humans and African elephants managed in free contact.